2019
DOI: 10.1002/hfm.20788
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of maximum endurance time for one‐handed carrying tasks

Abstract: The objective of this study was to establish models to predict maximum endurance time (MET) for one-handed carrying tasks. A one-handed carrying experiment, under three loads and two walking speeds, was performed. The participant carried a dumbbell on the side using either dominant or nondominant hand. His or her arm was straight-down.The MET values were collected. Both power and exponential functions were adopted in establishing simplified MET models considering the relative force (f MVC ) applied. The simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…The effects of walking speed on the MET were more prominent at low f MVC_back than were at a high one. This was consistent with the findings in the literature [35]. The MET model established in the current study may be used to determine the work/rest allowance for backpacking tasks similar to ours.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The effects of walking speed on the MET were more prominent at low f MVC_back than were at a high one. This was consistent with the findings in the literature [35]. The MET model established in the current study may be used to determine the work/rest allowance for backpacking tasks similar to ours.…”
Section: Discussionsupporting
confidence: 91%
“…Establishment of MET models has been reported [14,19,25,26,27,28,29,30,31,32,33]. Model development involves establishing a mathematical function with the %MVC, or alternatively the relative force ( f MVC = %MVC/100), as independent variable [23,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean absolute deviation (MAD) has been adopted to estimate the fitness of the model in estimating the MET (Li, Peng, et al, 2019;. The MADs of the MET models in the current study and those in the literature are shown in Table 6.…”
Section: Discussionmentioning
confidence: 99%